2009
DOI: 10.1016/j.meegid.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to chronic wasting disease in free-ranging white-tailed deer: Complement component C1q and Prnp polymorphisms

Abstract: The genetic basis of susceptibility to chronic wasting disease (CWD) in free-ranging cervids is of great interest. Association studies of disease susceptibility in free-ranging populations, however, face considerable challenges including: the need for large sample sizes when disease is rare, animals of unknown pedigree create a risk of spurious results due to population admixture, and the inability to control disease exposure or dose. We used an innovative matched case-control design and conditional logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 58 publications
0
29
1
Order By: Relevance
“…Haplotypes rather than diplotypes were examined as previous studies found one copy of the protective mutations sufficient to cause a measurable effect[36]. Management of deer is typically coordinated by county; therefore, we grouped deer according to the county of harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Haplotypes rather than diplotypes were examined as previous studies found one copy of the protective mutations sufficient to cause a measurable effect[36]. Management of deer is typically coordinated by county; therefore, we grouped deer according to the county of harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Even with high levels of CWD exposure, the effects of selection on cervid PrP genotype frequencies could take decades [133], maybe even centuries [134] to manifest. Further, selection may not elicit a strong genotype shift in cervids because PrP genotypes do not confer complete resistance, but merely extend CWD incubation period [135], and susceptible animals would therefore have opportunities to reproduce before infection or during clinical progression [136]. As such, it has been suggested that partially resistant PrP genotypes could ultimately exacerbate CWD epidemics by prolonging the time period for dispersal-mediated spread or prion shedding into the environment [135].…”
Section: Selection Acts On Prion Genes and Prion Variantsmentioning
confidence: 99%
“…Consequently it is clear that, to explain the observations in elk and deer reviewed here, we need to move beyond a tally of polymorphisms of the prion protein gene and examine other loci in conjunction with prnp allelic variations. Recently, Blanchong et al [85] have investigated polymorphisms in complement component C1q for association with CWD susceptibility and progression, and Ernest et al [86] have developed kinship analysis tools using microsatellite data and mitochondrial DNA sequence haplotypes that will allow finer analysis of factors influencing genetically linked transmission of CWD among white-tailed deer.…”
Section: Genetic Susceptibility Of Cervids To Cwdmentioning
confidence: 99%